Preparing Students for the Future of Pakistan in the Context of English Language Learning - Dr Anila Fatima Shakil; Dr Rabia Abdul Karim; Ms Salma Niazi (Al-Qanṭara, 2023)
English is taught as mandatory subject in all educational institutes. The objective of the study is that content and language integrated learning (CLIL) incorporated with ESP courses can lead students towards better learning as well as improved spoken English. The study is based on the fact that English language courses are showing clear relevance of the language and the future needs. It would definitely foster the process of learning with increased motivation. It is clearly not a waste of time and money if students are taught language functions and skills relevant to the need of future professions. Within a qualitative paradigm, the study is identified with Action Research (AR). The data collected by the respondents were studied and analyzed through SPSS; it was found through the results that language learning would be fun and more convenient if it meets the desired need of a future professional career.